Business Tax Policy under Default Risk - Nicola Comincioli; Sergio Vergalli; Paolo M. Panteghini (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this article we use a stochastic model with one representative firm to study business tax policy under default risk. We will show that, for a given tax rate, the government has an incentive to reduce (increase) financial instability and default costs if its objective function is welfare (tax revenue).
Keywords: H25; G33; G38; 330; Capital Structure; Default Risk; Business Taxation and Welfare